Bone marrow-derived mesenchymal stem cells and the tumor microenvironment - Bergfeld, Scott A.; DeClerck, Yves A. (Cancer and metastasis reviews, 2010)
Over the last decade, there has been a growing interest in the role of mesenchymal stem cells (MSC) in cancer progression. These cells have the potential to give rise to a variety of mesenchymal cells like osteoblasts, chondrocytes, adipocytes, fibroblasts, and muscle cells. In contrast to their hematopoetic counterparts, MSC are not as clearly defined, which makes the interpretation of their role in cancer progression more complex. However, the nature of the relationship between MSC and tumor cells appears dual. Primary and metastatic tumors attract MSC in their microenvironment where they become tumor-associated fibroblasts, affect tumor cell survival and angiogenesis, and have an immunomodulatory function, and vice versa in the bone marrow MSC attract tumor cells and contribute to a microenvironment that promotes osteolysis, tumor growth, survival, and drug resistance. Whether MSC are pro- or anti-tumorigenic is a subject of controversial reports that is in part explained by the complexity of their interaction with tumor cells and the large range of cytokines and growth factors they produce. The study of these interactions is a fertile ground of investigation that—as already demonstrated in the case of myeloma—should lead to novel therapeutic approaches in cancer. In this article, the biology and role of MSC in cancer is reviewed with a primary focus on bone marrow-derived MSC.